#FeesMustFall: Lessons from the Post‑colonial Global South (Journal of Student Affairs in Africa, 2021)
The protests that engulfed South African universities in 2015 and 2016 revealed a dissatisfaction by students with regard to higher education fees. The current study looks at some of the lessons that could assist South Africa in understanding the role of universal fee-free higher education or fee-free higher education for the poor. Most countries in the post-colonial global South indicate a shift into cost sharingas mounting financial pressures on state budgets make universal free education unsustainable. The current study shows that the cost sharing model in South Africa has not resonated with students and may also be exclusionary to poor students. The lessons from the post-colonial global South show that the trend in higher education is that the poor are often left out of most fee structures - including dual track, universal fee-free, and cost-sharing models. The current study explores some implications and considerations of the current means test model that has been introduced by the current South African president, while using the global South as reference point for the implications of this fee structure, particularly in relation to poor and working-class students.
Keywords: cost-sharing; funding; #FeesMustFall; global South; higher education; students; student movement; student politics